The effects of age and dietary resistant starch on digestibility, fermentation end products in faeces and postprandial glucose and insulin responses of dogs - Ribeiro, Érico de Mello [UNESP]; Peixoto, Mayara Corrêa [UNESP]; Putarov, Thaila Cristina [UNESP]; Monti, Mariana [UNESP]; Pacheco, Peterson Dante Gavasso [UNESP]; Loureiro, Bruna Agy [UNESP]; Pereira, Gener Tadeu [UNESP]; Carciofi, Aulus Cavalieri [UNESP] (Taylor & Francis, 2019)
The same food formulation processed to obtain two different starch gelatinisations (SG) and resistant starch (RS) contents was evaluated in old and adult dogs, regarding apparent total tract digestibility (ATTD) of nutrients, fermentation products in faeces, and postprandial glucose and insulin responses. A diet with corn was ground and extruded in two different ways, obtaining Low RS (2.2 g/kg DM; 99.9% of SG) and High RS (15.3 g/kg DM; 62.6% of SG). Each diet was fed to adults (4.0 ± 0.7 years) or old beagle dogs (11.5 ± 0.4 years) in a 2 (ages) x 2 (RS amounts) factorial arrangement with 8 dogs per food. Data were evaluated by analysis of variance, and postprandial responses by analysis of variance of repeated measurements over time (p < 0.05). Diet × age interaction was observed for protein ATTD, with lower values for old dogs fed High RS than those for the other treatments (p < 0.05). No age or diet effect was verified for the ATTD of other nutrients and faecal score. Faecal moisture and pH were higher for adults than that for old dogs (p < 0.05). The High RS food increased acetate, propionate and butyrate concentrations in faeces, regardless of age (p < 0.01). Old dogs presented lower acetate and total short-chain fatty acids (SCFA) and higher lactate and ammonia than adults (p < 0.05). Only for old dogs the intake of the High RS food reduced ammonia and increased faecal lactate (p < 0.05). An age × diet interaction was verified for glucose postprandial response, with lower values for old dogs fed High RS food (p < 0.05), while no differences were found for the other treatments. Old dogs had higher postprandial insulin secretion regardless of the diet (p < 0.05), and lower insulin increment at 180 min after the meal when fed the Low RS than when fed the High RS food (p < 0.05). In conclusion, the diet with lower SG and higher RS improved the intestinal microenvironment, with higher butyrate and total SCFA without altering faeces production or score. Old dogs presented less acetate and total SCFA and higher lactate and ammonia in faeces than adults. The High RS food increased lactate and reduced ammonia in faeces of old dogs, with possible positive influences for gut health. Old dogs had higher postprandial insulin secretion than that of adults to maintain blood glucose, and the diet with higher RS content reduced the postprandial glucose response of old dogs.
Keywords: Digestibility; dogs; extrusion; fermentation products; insulin secretion; physiological age; resistant starch